Deep surface Cu depletion induced by K in high‐efficiency Cu(In, Ga)Se2 solar cell absorbers. (25th March 2018) - Donzel‐Gargand, Olivier; Thersleff, Thomas; Keller, Jan; Törndahl, Tobias; Larsson, Fredrik; Wallin, Erik; Stolt, Lars; Edoff, Marika
Abstract: In this work, we used K‐rich glass substrates to provide potassium during the coevaporation of Cu(In, Ga)Se2 (CIGS) absorber layers. Subsequently, we applied a postdeposition treatment (PDT) using KF or RbF to some of the grown absorbers. It was found that the presence of K during the growth of the CIGS layer led to cell efficiencies beyond 17%, and the addition of a PDT pushed it beyond 18%. The major finding of this work is the observation of discontinuous 100‐ to 200‐nm‐deep Cu‐depleted patches in the vicinity of the CdS buffer layer, correlated with the presence of K during the growth of the absorber layer. The PDT had no influence on the formation of these patches. A second finding concerns the composition of the Cu‐depleted areas, where an anticorrelation between Cu and both In and K was measured using scanning transmission electron microscopy. Furthermore, a steeper Ga/(In+Ga) ratio gradient was measured for the absorbers grown with the presence of K, suggesting that K hinders the group III element interdiffusion. Finally, no Cd in‐diffusion to the CIGS layer could be detected. This indicates that if CdCu substitution occurs, either their concentration is below our instrumental detection limit or its presence is contained within the first 6 nm from the CdS/CIGS interface. Abstract : We study Cu‐depleted patches that appear at the surface of the Cu(In, Ga)Se2 absorber layer when K can diffuse from the substrate during the coevaporation. The transmission electron microscopy analysis reveals that the Cu‐depleted patches are enriched in both K and In and actually suggests that K is integrated in the CIGS lattice.